O desenvolvimento argumentativo na escrita e na oralidade: um estudo a partir da redação do ENEM e do júri simulado - Groos, Paola Tassinari (2022)
Argumentation is part of human activity and is carried out through orality and writing; therefore, it is essential that this practice is taught in school. This study is linked to the Postgraduate Program in Language and Literature at Federal University of Santa Maria (UFSM), to the research line Language in the social context, and to the research group Oral and written genres: theory and teaching (GOE). It aims to investigate the argumentative development of the "student-users‖ of Portuguese language using oral corpora – genres involved in the simulated jury – and written corpora – National High School Exam (ENEM) essays – produced in activities based on the continuum between oral and written genres in Portuguese language workshops. The ENEM essay and the argumentative genres of the simulated jury are the genres investigated in the school context. This research has as theoretical assumptions the perspectives on language from Bakhtin (1997; 2014) and on teaching from Vygotsky (1984; 1991). As for genre studies, this investigation was mainly based on Bakhtin (1997), Dolz and Schneuwly (2004), and Marcuschi (2001, 2008). In relation to argumentation studies, this research is anchored in the New Rhetoric, whose fundamental authors are Perelman and Olbrechts-Tyteca (1996) as well as Brazilian linguists such as Fiorin (2018) and Koch and Elias (2016). The methodology used to conduct this investigation in the classroom is action research (THIOLLENT, 1996; TRIPP, 2005; GREENWOOD and LEVIN, 2006), since it enables interaction between the researcher and the subjects. Thus, for generating the research corpus, we visited a state school in the municipality of Santa Maria, Rio Grande do Sul, Brazil, more specifically in a 12-grade class during the night shift. Nineteen workshops were held and two research subjects were chosen: A1 and A2. We analyzed five ENEM essays from A1 and three from A2, and their participation as a prosecutor and a defense attorney, respectively, in the simulated jury trial. Results point out to the argumentative level of students both in writing and orality and show the teaching of argumentation in Basic Education in Portuguese classes must be carried out through oral genres and written genres.